Implementation of Public Street Lighting Needs on the Sukabumi Southern Ring Road - Nanda Ikhwan Khair; Utamy Sukmayu Saputri; Ardin Rozadi; Muhammad Hidayat; Oksana Viktorovna Zadorozhnaya (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2021)
Ruas Lingkar Selatan is made to facilitate the mobility of people from Bogor to Cianjur and vice versa without having to pass the jammed roads of Sukabumi city. However, the traffic signs, in Ruas Lingkar Selatan of Sukabumi City has not met the elements of comfort, safety, smoothness, and road safety. In addition, the traffic signs, which is located in Ruas Lingkar Selatan of Sukabumi City, is not complete and does not meet the standards. The purpose of this study was to determine the need for traffic signs, criteria needed on the road ruas lingkar selatan. The regulation used to solve this problem is SNI 7391 2008 concerning specifications for street lighting in urban areas. Availability of sufficient lighting is one of the supporting aspects of safety in driving on the highway. Apart from lighting the vehicle itself, the availability of street lighting or commonly known as public street lighting is very important and must be considered properly. Ideally the lights installed are high pressure sodium gas (SON) 250 watts, continuous and partial lamp placement systems, the distance between the traffic signs, poles ruas lingkar selatan is 39 meters with a lighting quality of 10 LUX¸ the lamp poles used are double light poles which is placed in the median of the road, PJU uses solar panels, and in meeting road service standards to be ideal, 317 traffic signs needed.